2007
DOI: 10.1111/j.1399-0004.2007.00810.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic testing for heart disease susceptibility: potential impact on motivation to quit smoking

Abstract: As genetic tests for common gene variants and multifactorial, lifestyle-related conditions become available, it will be increasingly important to determine the psychological and behavioral impact of this emerging class of genetic tests. Our aim was to examine the potential impact of genetic testing for heart disease susceptibility on psychological predictors of smoking cessation. Two hundred and sixty-one smokers were asked to imagine that they had undergone a test for heart disease risk. They were randomly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…For those who underwent genetic testing for diabetes, myocardial infarction, and cancer, there has been little or no effect on longterm abstinence of smoking or short-term changes in diet and exercise. 22,28,32 There are concerns that negative genetic test results for CVD may lead to false reassurance, while positive results may induce unnecessary anxiety in others. 33 In this study, the false reassurance was identified but not related to above-average results.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For those who underwent genetic testing for diabetes, myocardial infarction, and cancer, there has been little or no effect on longterm abstinence of smoking or short-term changes in diet and exercise. 22,28,32 There are concerns that negative genetic test results for CVD may lead to false reassurance, while positive results may induce unnecessary anxiety in others. 33 In this study, the false reassurance was identified but not related to above-average results.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…[23][24][25][26][27] Participants' opinions have also been ascertained in hypothetical scenarios. 28,29 In this study, a perceived familial risk of CHD was a major driver for requesting genetic testing. This parallels the findings in studies of heart disease and breast cancer in secondary care.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…We utilized a common vignette paradigm that asks individuals to consider different hypothetical scenarios for genetic testing. [21][22][23] …”
Section: Introductionmentioning
confidence: 99%
“…Two analog studies were published by Sanderson and coworkers (2005;Sanderson and Michie 2007) analyzing hypothetical smoking cessation rates and attitudes towards smoking behavior. In the study by Sanderson and Michie (2007) addressing genetic testing for heart disease susceptibility, 261 smokers were randomized into three groups.…”
Section: Smoking Cessationmentioning
confidence: 99%
“…In the study by Sanderson and Michie (2007) addressing genetic testing for heart disease susceptibility, 261 smokers were randomized into three groups. Of the participants, 96 received a genetic high-risk result for heart disease and 79 a genetic low-risk result for heart disease.…”
Section: Smoking Cessationmentioning
confidence: 99%